Hearing voices: Reconciling scale and gender in agricultural research - Lannerstad, Mats (International Livestock Research Institute, 2016)
Mats Lannerstad is currently working on two major projects that incoroprate gender. One is funded by the Bill and Melinda Gates Foundation; it assesses the environmental imapcts of development projects. The researchers ask local stakeholders to contribute in various stages of the process, analysis and recommendations. They now consider gender issues in this work. A second grant, from the UK Department for International Development is looking at gender equity and dynamics. The research team is also trying to develop a framework that captures social equity and gender dimensions at the landscape level. Interview with Mats Lannerstad (ILRI) for the book "A different kettle of fish? Gender integration in livestock and fish research". http://hdl.handle.net/10568/76684